How Safe Are Nepal’s Roads? A Study of Road Safety Legislation and WHO Standards - Dhungana, Subigya; Magar, Pramila Thapa; Dhungana, Bharat Ram (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.005Around the world, traffic accidents result in significant catastrophes. The consequences of traffic accidents go far beyond the immediate suffering of the individuals involved. This paper aims to examine the road safety legislation and WHO standards adopted in Nepal. The paper is based on secondary data and policy documents related to road safety and WHO standards in the context of Nepal. It presents Nepal’s road network, significant improvements in road safety indicators, and encouraging advancements in road safety. The study finds five major areas for improvement in road safety laws in Nepal: seat-belt regulations, helmet laws, speed laws, child restraint laws, and drinking and driving laws. The study also reveals that Nepal’s current regulatory framework needs to be improved by monitoring actual appropriate helmet fastening and standardization. There is a lack of precise BAC restrictions for drivers and insufficient speed limits under WHO recommendations. Nepal’s child restraint rules also need to be expanded to include seat belt usage in all cars and forbid children from sitting in the front seats. To close those regulatory gaps and protect Nepalese citizens’ safety on the roads, it ends by providing a strict set of recommendations, such as increased enforcement, public awareness campaigns, and changes to road design and concrete making plans. Policymakers, researchers, and stakeholders working to promote street safety measures in Nepal and abroad would find great assistance from this article, which offers a detailed examination and smart recommendations.